2017
DOI: 10.3892/mmr.2017.8096
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic effects of mesenchymal stem cells combined with short hairpin RNA on liver injury induced by hepatitis B virus infection

Abstract: The clinical symptoms of chronic hepatitis B virus (HBV) infection include severe liver damage, which is associated with the elimination of the HBV-infected cells by the immune system. It has been suggested that suppression of HBV replication is not sufficient for patients with hepatitis B and the damaged liver function requires restoration. In the present study, mesenchymal stem cells (MSCs) were combined with short hairpin (sh)RNA to treat liver injury and suppress HBV replication in a mouse model. Lx-shRNA1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 41 publications
(48 reference statements)
0
1
0
Order By: Relevance
“…In a pre-clinical model, Liu et al [ 117 ] reported that transplantation of MSCs expressing short hairpin RNA against hepatitis viral proteins (HBV S and HBV X) significantly reduced HBV antigens in the liver and serum. Masalova et al [ 179 ] tested the efficacy of utilizing MSCs as an immunization agent against HCV and found that murine BM-MSCs expressing five non-structural HCV proteins induced significantly higher proliferation of lymphocytes, IFN-γ secretion, and IgG2a levels compared to naked DNA immunizations suggesting the feasibility of utilizing modified MSCs as vaccine agents.…”
Section: Genetic Modifications and Priming Of Mscsmentioning
confidence: 99%
“…In a pre-clinical model, Liu et al [ 117 ] reported that transplantation of MSCs expressing short hairpin RNA against hepatitis viral proteins (HBV S and HBV X) significantly reduced HBV antigens in the liver and serum. Masalova et al [ 179 ] tested the efficacy of utilizing MSCs as an immunization agent against HCV and found that murine BM-MSCs expressing five non-structural HCV proteins induced significantly higher proliferation of lymphocytes, IFN-γ secretion, and IgG2a levels compared to naked DNA immunizations suggesting the feasibility of utilizing modified MSCs as vaccine agents.…”
Section: Genetic Modifications and Priming Of Mscsmentioning
confidence: 99%